Factors Related to The Response Time of Handling Emergency Cases in The Eranger Installation Room - Haryani, Farida (Rifa'Institute, 2024)
Introduction: Response time depends on the speed available and the quality of providing assistance to save lives/prevent disability. Objective: The purpose of the study was to determine the factors related to the Response Time of nurses in handling emergency patients at the ER Harapan Insan Hospital Sendawar West Kutai Regency. Method: Research with cross sectional approach. sample selection with purposive sampling of 26 respondents. Data analysis technique chi square test at a significance level of 95% (a 0.05). Results and Discussion: The research found that most of the nurses had Response Time < 5 minutes as many as 22 (86.4%). Statistical tests showed that there was a relationship between training (? 0.001) and compensation (? 0.028) with the response time for handling emergency cases at Harapan Insan Sendawar Hospital. Conclusion: The nurse's response time in handling emergency cases at the Emergency Installation Harapan Insan Sendawar General Hospital is on average <5 minutes. Training and rewards are related to nurse response time, while length of work and motivation have nothing to do with nurse response time in handling emergency patients in the Emergency Installation HIS Hospital.